Draught Animals and their Management: The Future in Rain-fed Agriculture - Pearson, R A (Annals of Arid Zone, 2016)
The use of animal power in rain-fed crop production can increase farm productivity, through increased area cultivated, yield per farm and improved access to markets. Farmers maintaining animals for work need to ensure that they integrate effectively into their farming system, to make the best use of feed resources, bearing in mind the diminishing availability of grazing land, increasing population pressure and changing demands for meat and milk. Low quality forage is a feature of most systems and the diet of working animals can be constrained by low feed supplies at the end of the dry season, the time when the animals are often required to do most work. This review examines the ways in which farmers can modify their feeding and management practices to cope with the above factors and maintain agricultural productivity. Some examples of management systems where animals are kept for work alone, and for work and meat/milk production, are also described.